Digital revolutions in public finance - Gupta, Sanjeev; Keen, Michael; Shah, Alapa; Verdier, Genevieve; International Monetary Fund (Washington, D.C International Monetary Fund (IMF), 2017)
Digitization promises to reshape fiscal policy by transforming how governments collect, process, share, and act on information. More and higher-quality information can improve not only policy design for tax and spending, but also systems for their management, including tax administration and compliance, delivery of public services, administration of social programs, public financial management, and more. Countries must chart their own paths to effectively balance the potential benefits against the risks and challenges, including institutional and capacity constraints, privacy concerns, and new avenues for fraud and evasion
​Acknowledgments -- Foreword -- Contributors -- 1 Introduction: Reshaping Public Finance / Sanjeev Gupta, Michael Keen, Alpa Shah, and Geneviève Verdier -- PART I PUSHING THE FRONTIERS IN TAX POLICY AND REVENUE ADMINISTRATION -- 2 Digitalization and Taxation / Bas Jacobs -- 3 Taxation and the Peer-to-Peer Economy / Aqib Aslam and Alpa Shah -- 4 Implications of Digitalization for International Corporate ax Reform / Michael P. Devereux and John Vella -- 5 Testing and Implementing Digital Tax Administration / Jingnan (Cecilia) Chen, Shaun Grimshaw, and Gareth D. Myles -- PART II INNOVATIONS IN FISCAL MANAGEMENT -- 6 Nowcashing: Using Daily Fiscal Data for Real-Time Macroeconomic Analysis / Florian Misch, Brian Olden, Marcos Poplawski-Ribeiro, and Lamya Kejji -- 7 Instilling Digital Trust: Blockchain and Cognitive Computing for Government / Arvind Krishna, Martin Fleming, and Solomon Assefa -- PART III MODERNIZING PUBLIC SERVICE DELIVERY AND SPENDING -- 8 Using Digital Technolog for Public Service Provision in Developing Countries: Potential and Pitfalls / Jenny C. Aker -- 9 The Digital Revolution and Targeting Public Expenditure for Poverty Reduction / Ravi Kanbur -- PART IV COUNTRY CASE STUDIES -- 10 Digitalization in Kenya: Revolutionizing Tax Design and Revenue Administration / Njuguna Ndung'u -- 11 Fiscal Policy Consequences of Digitalization and Demonetization in India / Rathin Roy and Suyash Rai -- 12 Integration of Government Digitalization and Public Financial Management—Initial Evidence / Marco Cangiano, Alan Gelb, and Ruth Goodwin-Groen -- PART V HOW MUCH IS IT ALL WORTH? -- 13 The Value of Digitalizing Government Payments in Developing Economies / Susan Lund, Olivia White, and Jason Lamb -- Index
Includes bibliographical references and index
Keywords: Public finance; FISCAL POLICY; PUBLIC FINANCE; Tax administration and procedure